2016
DOI: 10.1016/j.jmb.2016.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Shut-Down by 16S rRNA Fragmentation in Stationary-Phase Escherichia coli

Abstract: Stationary-phase bacterial cells are characterized by vastly reduced metabolic activities yielding a dormant-like phenotype. Several hibernation programs ensure the establishment and maintenance of this resting growth state. Some of the stationary phase-specific modulations affect the ribosome and its translational activity directly. In stationary-phase Escherichia coli, we observed the appearance of a 16S rRNA fragmentation event at the tip of helix 6 within the small ribosomal subunit (30S). Stationary-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…Taken together, we found a substantial alteration in the rRNA/protein ratios of extracts from different in vivo backgrounds. Nevertheless, in contrary to other studies that detected a fragmentation of rRNA in stationary E. coli 41 , the CGE-LIF analysis showed only intact 16 S and 23 S rRNA (Supplemental Fig. S2 ), suggesting that rRNA integrity is conserved.…”
Section: Resultscontrasting
confidence: 99%
“…Taken together, we found a substantial alteration in the rRNA/protein ratios of extracts from different in vivo backgrounds. Nevertheless, in contrary to other studies that detected a fragmentation of rRNA in stationary E. coli 41 , the CGE-LIF analysis showed only intact 16 S and 23 S rRNA (Supplemental Fig. S2 ), suggesting that rRNA integrity is conserved.…”
Section: Resultscontrasting
confidence: 99%
“…Both sites are exposed on the surface of the ribosome and the cleavage within helix 6 of 16S rRNA in the stationary phase ribosomes was recently reported. 49 As activation of MazF, 50,51 and the cleavage of 16S rRNA at #1500 ACA 28 were reported in stress conditions, we expected to identify the truncated 3 0 -end of 16S rRNA at A1499 and verify the presence of the stress ribosomes upon stress. Therefore, we applied 3 0 -RACE and Northern hybridization to analyze the RNA from stationary phase cells, CAM treated cultures and cultures where amino acid starvation was induced by mupirocin (MUP).…”
Section: Validation Of the Rna-seq Resultsmentioning
confidence: 94%
“…It was recently shown that cleavages within the helix 6 of 16S rRNA reduce the performance of stationary phase ribosomes. 49 At the same time, in many bacterial species, rRNA is normally discontinuous and is formed through excision of intervening sequences (IVS) which are located in the same variable helices. [59][60][61] Sequence tags have been inserted into these helices with no deleterious effects, 62 63 and when a Salmonella IVS was inserted into the helix 45 of E. coli 23S rRNA, it was excised by RNase III while the ribosomes retained functionality.…”
Section: Discussionmentioning
confidence: 99%
“…This process, termed as ribosome hibernation, is thought to be a mechanism to fine-tune the translation process according to environmental conditions ( McKay and Portnoy, 2015 ). Recently, 16S rRNA fragmentation at the tip of helix 6 has been shown to attenuate the activity of 30S ribosomal subunit and thereby protein synthesis ( Luidalepp et al, 2016 ). Also, during limited nutrient availability, accumulation of truncated mRNA and deacylated tRNA occurs.…”
Section: Physiology Of the Stationary Phasementioning
confidence: 99%